MODEL DIGITAL STORYTELLING DALAM PEMBELAJARAN BAHASA ARAB MELALUI YOUTUBE 'BELAJAR BAHASA ARAB DARI NOL - Akmal Varras Amrulloh Akmal Varras; Alfina Arofatul B Alfina; Denmas Azkal Basyari Arsyad Denmas (DAS Institute, 2026)
This study examines the application of the Digital Storytelling (DST) model in Arabic language learning, focusing on the video